2016
DOI: 10.1007/s40735-016-0036-1
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Ti/HA in Saliva at Different Temperatures as Restorative Materials

Abstract: Titanium and hydroxyapatite (HA) are wellknown materials applied as biomaterials. Ti shows good mechanical properties and corrosion resistance, whereas HA possesses excellent biocompatibility and bioactivity but weak mechanical properties. The combination of the Ti and HA properties is expected to produce good corrosion resistance. Corrosion behavior of Ti/HA as composite (70Ti/30HA) and functionally graded material (Ti/HA FGM with five layers) has been investigated in saliva at pH 4.4 at five temperatures 10,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…In the murine system, however, CD8 + cytotoxic T lymphocytes (CTLs) rely on granule exocytosis and CD4 + CTLs resort to the Fas and Fas ligand (FasL) pathway to mediate cytotoxicity [57,58], whereas in the human system, CTLs (both CD8 + and CD4 + ) predominantly utilize the cytolytic perforin and granzyme axis to mediate target cell apoptosis [59]. In addition, when equipped with a CAR, human T cells of both subsets can effectively eradicate tumor cells in a MHC- and Fas-independent manner [60,61].…”
Section: Perforin and Granzymementioning
confidence: 99%
“…In the murine system, however, CD8 + cytotoxic T lymphocytes (CTLs) rely on granule exocytosis and CD4 + CTLs resort to the Fas and Fas ligand (FasL) pathway to mediate cytotoxicity [57,58], whereas in the human system, CTLs (both CD8 + and CD4 + ) predominantly utilize the cytolytic perforin and granzyme axis to mediate target cell apoptosis [59]. In addition, when equipped with a CAR, human T cells of both subsets can effectively eradicate tumor cells in a MHC- and Fas-independent manner [60,61].…”
Section: Perforin and Granzymementioning
confidence: 99%
“…In addition, the existence of Ca 5 (PO 4 ) 3 (OH), Ca 4 O(PO 4 ) 2 , CaTi 4 (PO 4 ) 6 , etc., which were mentioned in other literatures [ 15 , 16 , 51 , 52 , 53 ], were not detected by XRD ( Figure 4 ). Moreover, a small amount of Ti 17 P 10 , CaTiO 3 , Ca 3 (PO 4 ) 2 were detected.…”
Section: Discussionmentioning
confidence: 62%
“…Compared with coating, there are similar complex chemical reactions in uncoated composite. Researchers revealed that some new phases, such as Ca 5 (PO 4 ) 3 (OH), CaTiO 3 , Ti x P y , β-Ti, Ti 2 O, CaO, Ca 4 O(PO 4 ) 2 , Ca 3 (PO 4 ) 2 (TCP), CaTi 4 (PO 4 ) 6 , etc., have appeared in Titanium alloys/HA composites prepared by powder metallurgy and other methods [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. The presence of calcium titanate produced by the reaction between Titanium and HA showed the existence of interfacial chemical reactions [ 27 ].…”
Section: Interfacial Characteristics Of Titanium Alloy/ha Compositmentioning
confidence: 99%
“…However, there are some problems such as stress shielding phenomenon, complex reactions, and so on [ 1 , 4 , 5 , 6 ]. Research showed that there were some new phases such as Ca 5 (PO 4 ) 3 (OH), CaTiO 3 , Ti x P y , β-Ti, Ti 2 O, CaO, Ca 4 O(PO 4 ) 2 , Ca 3 (PO 4 ) 2 (TCP), and CaTi 4 (PO 4 ) 6 in Ti alloy/HA composites after high temperature sintering [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. It reveals that there are complex reactions between Ti and HA when sintered at a high temperature.…”
Section: Introductionmentioning
confidence: 99%